2019
DOI: 10.1001/jamanetworkopen.2018.6847
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Rates Following Cytoreductive Surgery Combined With Hyperthermic Intraperitoneal Chemotherapy Compared With Other High-Risk Surgical Oncology Procedures

Abstract: Key Points Question What are the morbidity and mortality of cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) compared with other major oncologic surgical procedures? Findings In this cohort study of 1822 patients who received CRS/HIPEC compared with patients who received other high-risk surgical oncology procedures, overall 30-day mortality was lower in CRS/HIPEC (1.1%) compared with pancreaticoduodenectomy (2.5%), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 43 publications
8
103
0
Order By: Relevance
“…2 This is understandable due to the fact that the learning curves of both of these complex procedures are steep and are being simultaneously developed as a program evolves. 3,4 In our opinion, there should be a standardized adaptable learning curve that takes into consideration the following concepts.…”
Section: E T T E R T O T H E E D I T O R Crs and Hipec: The Need Fomentioning
confidence: 99%
See 1 more Smart Citation
“…2 This is understandable due to the fact that the learning curves of both of these complex procedures are steep and are being simultaneously developed as a program evolves. 3,4 In our opinion, there should be a standardized adaptable learning curve that takes into consideration the following concepts.…”
Section: E T T E R T O T H E E D I T O R Crs and Hipec: The Need Fomentioning
confidence: 99%
“…The learning curve should not be centered on the surgeon, but on the team of anesthesiologists, nurses, and surgeons and should be focused on the management of the preoperative phase and early recognition of the complications in the postoperative recovery. 4. In addition to technical skills, selecting the appropriate patients in multidisciplinary team meetings remains challenging, as this process mandates properly identifying patients who are unlikely to benefit from the procedure.…”
Section: E T T E R T O T H E E D I T O R Crs and Hipec: The Need Fomentioning
confidence: 99%
“…A recent retrospective study looked at a total of 34 114 patients who underwent either CRS + HIPEC, major liver resection, pancreaticoduodenectomy or esophagectomy between 2005 and 2015. 34 This study showed that in the 1822 patients who underwent CRS + HIPEC, overall 30-day mortality was 1.1%, median length of stay was 8 days and the need to return to the operation room was 6.8%. The comparative analysis of CRS + HIPEC to Intraoperative picture of what appears to be an extensive PMP on the left and where an extraperitoneal approach has been elected.…”
Section: Complicationsmentioning
confidence: 75%
“…It is well established that the complexity of CRS/HIPEC is comparable to other complex oncologic operations with a similar safety profile 27 . However, there is a significant learning curve in both technique and judgment, which is slightly higher than other complex oncological operations.…”
Section: Application Of Hyperthermic Intraperitoneal Chemotherapy Andmentioning
confidence: 99%